2018
DOI: 10.14814/phy2.13738
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity protects NLRP3 inflammasome-associated coronary vascular dysfunction in obese mice

Abstract: Activation of the nucleotide‐binding oligomerization domain‐like receptor family pyrin domain‐containing 3 (NLRP3) inflammasome mediates the release of pro‐inflammatory cytokine interleukin (IL)‐1β and thereby plays a pivotal role in the inflammatory response in vascular pathology. An active lifestyle has beneficial effects on inflammation‐associated vascular dysfunction in obesity. However, it remains unclear how physical activity regulates NLRP3 inflammasome‐mediated vascular dysfunction in obesity. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Studies have shown that exercise can reduce cardiac oxidative stress and NLRP3 inflammasome expression in ApoE -/- mice [ 37 ]. Lee et al [ 47 ] found that exercise training could reduce the upregulated expression of NLRP3 and its downstream cascade factors in an obese mouse model. In a diabetic mouse model, exercise restored endothelial nitric oxide synthase (eNOS) expression and nitric oxide (NO) production by reducing NLRP3 expression, thereby eliminating downstream products of NLRP3 activation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exercise can reduce cardiac oxidative stress and NLRP3 inflammasome expression in ApoE -/- mice [ 37 ]. Lee et al [ 47 ] found that exercise training could reduce the upregulated expression of NLRP3 and its downstream cascade factors in an obese mouse model. In a diabetic mouse model, exercise restored endothelial nitric oxide synthase (eNOS) expression and nitric oxide (NO) production by reducing NLRP3 expression, thereby eliminating downstream products of NLRP3 activation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients having an “inflammaging,” a low grade inflammation associated with NLRP3 inflammasome priming and activation and weaker inhibition ( 24 ) and, obese patients with a metainflammation ( 25 ) resulting in a higher base activity of NLRP3 ( 26 , 27 ). An enhanced exposure to DAMPs and NLRP3 inflammasome activation can affect immune fitness and is the result of a complex interplay where genetics [SNPs in NLRP3 ( 28 )] and also lifestyle factors [such as exercise, reduce NLRP3 activation ( 29 ), certain diets, block or stimulate NLRP3 activation ( 30 , 31 ) and, air pollution, induces NLRP3 activation ( 32 )] are interconnected.…”
Section: Scenarios Of Covid-19 Immune Responsementioning
confidence: 99%
“…Plasma levels of adiponectin (APN) are increased by regular physical exercise (Saeidi et al, 2020; Zouhal et al 2021). APN binds to adiponectin receptor 1 (AdipR1) in endothelial cells, mitigating the induction of inflammasomes, especially NLPR3, whose signals include activation of caspase-1 and IL-1β ( Du et al, 2016 ; Hui et al, 2012 ; Lee et al, 2020 ; Lee et al, 2018 ; Lee et al, 2011 ). Downregulated inflammasomes attenuate ROS production in endothelial cells.…”
Section: Exercise Improves Thermoregulationmentioning
confidence: 99%